Phase behaviour of the confined lattice gas Lebwohl-Lasher model - Almarza, N.G.; Martín, C.; Lomba, E. (Condensed Matter Physics, 2013)
The phase behaviour of the Lebwohl-Lasher lattice gas model (one of the simplest representations of a nematogenic fluid) confined in a slab is investigated by means of extensive Monte Carlo simulations. The model is known to yield a first order gas-liquid transition in both the 2D and 3D limits, that is coupled with an orientational order-disorder transition. This latter transition happens to be first order in the 3D limit and it shares some characteristic features with the continuous defect mediated Berezinskii-Kosterlitz-Thouless transition in 2D. In this work we will analyze in detail the behaviour of this system taking full advantage of the lattice nature of the model and the particular symmetry of the interaction potential, that allows for the use of efficient cluster algorithms. Фазова поведiнка граткової моделi Лебволя-Лашера (одне з найпростiших представлень нематогенного плину), що знаходиться мiж двома площинами, дослiджується за допомогою екстенсивних симуляцiй Монте Карло. Вiдомо, що модель дає фазовий перехiд газ-рiдина першого роду в двовимiрнiй i тривимiрнiй границях, який пов’язаний з орiєнтацiйним переходом лад-безлад. Останнiй є переходом першого роду в тривимiрнiй границi i має деякi спiльнi характеристичнi риси з неперервним дефектно опосередкованим переходом Березiнського-Костерлiца-Таулесса у двовимiрному випадку. В цiй роботi ми детально аналiзуємо поведiнку цiєї системи, використовуючи всi переваги ґраткової природи моделi i симетрiї потенцалу взаємодiї, якi дають змогу використати ефективнi кластернi алгоритми.